Omorgus suberosus and Polynoncus bifurcatus (Coleoptera: Scarabaeoidea: Trogidae) in exotic and native environments of Brazil - Correa,César M. A. (2013)
Trogidae beetles are important for the decomposition of organic material in ecosystems. In the Neotropical region, little is known about this family, except for their taxonomy. In this study, we report the presence of Omorgus suberosus (Fabricius, 1775) and Polynoncus bifurcatus (Vaurie, 1962) in exotic and native environments of Brazil, sampled with different baits. The beetles were captured in pastures with introduced grass (Brachiaria spp.) and in patches of native forest (Brazilian savanna). We used pitfall traps baited with carrion and human feces every two weeks, from January to December 2011, and with carrion, cow dung, human feces and pig manure at the beginning of the rainy season (October 2011). Over the course of one year, 24 individuals of O. suberosus were captured, 16 in the exotic and eight in the native environment, respectively. In the sampling performed at the beginning of the rainy season, 32 individuals of O. suberosus and seven of P. bifurcatus were obtained. Omorgus suberosus specimens were sampled in both environments, suggesting a possible tolerance to anthropogenic environments, as in the case of introduced grasses. Polynoncus bifurcatus individuals were captured only in native environments, which may indicate a strong relationship with more heterogeneous and/or relatively preserved habitats. We discuss such relationships in light of published data and new information provided here.